2018
DOI: 10.3390/su10093273
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Properties and Productivity under Different Tillage Practices and Wheat Genotypes: A Short-Term Study in Iran

Abstract: Natural resources are the most limiting factors for sustainable agriculture in Iran. Traditional practices are intensive tillage that leads to a negative impact on crop productivity and soil properties. Conservation agriculture including tillage reductions, better agronomy, and improved varieties, showed encouraging results. The goal of this study was to test combined effect of tillage practices and wheat (Triticum aestivum L.) genotypes on soil properties as well as crop and water productivity. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 80 publications
(122 reference statements)
8
33
3
Order By: Relevance
“…This could be related to the overall beneficial effect of no-tillage over reduced tillage on soil components (especially, for N-NO 3 − and P), saturation time and water infiltration. These observations are in agreement with other studies that have reported significant increases in soil N or water content under no-tillage [4,7,9,10]. Some modifications of soil properties might be associated not merely with the reduced breakdown of macro-aggregates but also with the slower decomposition of crop residues when no-tillage is practiced [6,9,66].…”
Section: Minimum Tillage Versus No-tillagesupporting
confidence: 92%
See 2 more Smart Citations
“…This could be related to the overall beneficial effect of no-tillage over reduced tillage on soil components (especially, for N-NO 3 − and P), saturation time and water infiltration. These observations are in agreement with other studies that have reported significant increases in soil N or water content under no-tillage [4,7,9,10]. Some modifications of soil properties might be associated not merely with the reduced breakdown of macro-aggregates but also with the slower decomposition of crop residues when no-tillage is practiced [6,9,66].…”
Section: Minimum Tillage Versus No-tillagesupporting
confidence: 92%
“…Some studies have reported a positive effect of no-tillage [7,12,67], whereas others have found negative effects [9,68] or no significant differences between both systems [69,70]. It must be noted that only the studies of Khorami et al [9] and Carr et al [70] were based on the analysis of more than one genotype (4 and 5, respectively) in different environments. Comparison of the mean GW values obtained for each variety under minimum tillage and no-tillage reveals different trends among the genotypes tested in the present study ( Figure 5).…”
Section: Minimum Tillage Versus No-tillagementioning
confidence: 99%
See 1 more Smart Citation
“…Moraru and Rusu (2012) examined the influence of CT, RT, and sowing with no-tillage (NT) and suggest that differences in wheat yield with these systems are nonsignificant. Khorami et al (2018) examined the effects of CT and RT and sowing with NT on several wheat genotypes and concluded that the highest yields were achieved in the RT system, followed by the CT system, while the lowest yields occurred in the NT system.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term reduced tillage or no-tillage farming often lead to increased soil compaction, which results in increased soil bulk density and reduced soil porosity and impedes root penetration [20][21][22]. For example, Khorami et al [23] found that no-tillage had higher soil bulk density at surface soil, thereby lowering cumulative water infiltration compared with CT practice. In the study region, CT operations are usually carried out before sugarcane planting and result in improved crop yield.…”
Section: Introductionmentioning
confidence: 99%